2006
DOI: 10.1080/14622200500431825
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of household smoking bans among Chinese Americans

Abstract: No population-based data are available on the degree to which Chinese Americans have adopted smoke-free household policies and whether these policies are effective in reducing environmental tobacco smoke (ETS) exposure. The present study examines the prevalence of smoke-free home rules among Chinese Americans living in New York City, describes predictors of adopting full smoking bans in the home, and explores the association between household smoking restrictions and ETS exposure at home. In-person interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 19 publications
6
36
3
Order By: Relevance
“…In the analysis, a total workplace ban was defined as Bsmoking not allowed anywhere.^Partial smoking ban effects were not analyzed because of consistent reports of the reduced effect of less comprehensive smoking restrictions on exposure to SHS and tobacco use behaviors compared with total bans. 14,22,23 Health status was measured using the standardized question BWould you say your health in general is excellent, very good, good, fair, or poor?^Chronic conditions were measured by whether the respondent had ever been told by a physician that they had the following: diabetes, bronchitis, emphysema, asthma, heart disease, high blood pressure, or cancer. Linguistic acculturation was measured by a composite of two categorical variables: speaks English in the home and/or reads English newspapers most or every day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis, a total workplace ban was defined as Bsmoking not allowed anywhere.^Partial smoking ban effects were not analyzed because of consistent reports of the reduced effect of less comprehensive smoking restrictions on exposure to SHS and tobacco use behaviors compared with total bans. 14,22,23 Health status was measured using the standardized question BWould you say your health in general is excellent, very good, good, fair, or poor?^Chronic conditions were measured by whether the respondent had ever been told by a physician that they had the following: diabetes, bronchitis, emphysema, asthma, heart disease, high blood pressure, or cancer. Linguistic acculturation was measured by a composite of two categorical variables: speaks English in the home and/or reads English newspapers most or every day.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Moreover, regional surveys conducted in Asian languages indicate that Chinese Americans are at high risk for excess tobaccorelated morbidity and mortality with smoking prevalence rates for men ranging from 28 to 36%. [12][13][14] Despite the magnitude of this population growth, there is lack of information on health measures and more specifically the impact of tobacco related policies on health status among Chinese Americans. Furthermore, there are no studies examining the relative effects of household and workplace smoking on health status among the native or foreign-born U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the data source and sample selection methods is reported elsewhere [13,14]. Briefly, eligible households were obtained from the Flushing and Sunset Park white pages, using a list of 867 unique Chinese surname spellings identified in consultation with Chinese linguists.…”
Section: Data Sources and Sample Selectionmentioning
confidence: 99%
“…Such change corresponds with evidence demonstrating shifts in health risk behaviors among immigrants groups as they adapt to U.S. culture and social structures. 16,34,35 Research indicates that traditional Chinese values support smoking among foreign-born Chinese American men. In China, smoking among men is highly valued and viewed as an important form of social and business etiquette.…”
Section: Changes In Smoking Behaviormentioning
confidence: 99%
“…14 This immigrant group is at particularly high risk for excess tobacco-related morbidity and mortality, with smoking prevalence ranging from 29% to 34% among Chinese American men. [15][16][17][18][19][20][21][22][23] While not focusing on Chinese Americans specifically, the NYC CHS found that 48% of AAPI smokers made a cessation-related behavior change in response to the 2002 taxes (unpublished data, NYC Department of Health and Mental Hygiene, 2003). Yet the study also found activities related to price avoidance.…”
mentioning
confidence: 99%